A Mutation in the 3-Phosphoglycerate Kinase Gene Allows Anaerobic Growth of Bacillus subtilis in the Absence of ResE Kinase - Nakano, Michiko M. (American Society for Microbiology, 1999)
The Bacillus subtilis ResD-ResE two-component signal transduction system is essential for aerobic and anaerobic respiration. A spontaneous suppressor mutant that expresses ResD-controlled genes and grows anaerobically in the absence of the ResE histidine kinase was isolated. In addition, aerobic expression of ResD-controlled genes in the suppressed strain was constitutive and occurred at a much higher level than that observed in the wild-type strain. The suppressing mutation, which mapped to pgk, the gene encoding 3-phosphoglycerate kinase, failed to suppress a resD mutation, suggesting that the suppressing mutation creates a pathway for phosphorylation of the response regulator, ResD, which is independent of the cognate sensor kinase, ResE. The pgk-1 mutant exhibited very low but measurable 3-phosphoglycerate kinase activity compared to the wild-type strain. The results suggest that accumulation of a glycolytic intermediate, probably 1,3-diphosphoglycerate, is responsible for the observed effect of the pgk-1 mutation on anaerobiosis of resE mutant cells.